Radiation dose reduction for chest CT with non-linear adaptive filters. (March 2013) - Singh, Sarabjeet; Digumarthy, Subba R; Back, Anni; Shepard, Jo-Anne O; Kalra, Mannudeep K
Background: CT radiation dose reduction results in increased noise or graininess of images which affects the diagnostic information. One of the approaches to lower radiation exposure to patients is to reduce image noise with the use of image processing software in low radiation dose images. Purpose: To assess image quality and accuracy of non-linear adaptive filters (NLAF) at low dose chest CT. Material and Methods: In an IRB approved prospective study, 24 patients (mean age, 63±7.3 years; M:F ratio, 11:13) gave informed consent for acquisition of four additional chest CT image series at 150, 110, 75, and 40 mAs (baseline image series) on a 64-slice MDCT over an identical 10-cm length. NLAF was used to process three low dose (110, 75, and 40 mAs) image series (postprocessed image series). Two radiologists reviewed baseline and postprocessed images in a blinded manner for image quality. Objective noise, CT attenuation values, patient weight, transverse diameters, CTDIvol, and DLP were recorded. Statistical analysis was performed using parametric and non-parametric tests for comparing postprocessed and baseline images. Results: No lesions were missed on baseline or postprocessed CT images ( n = 80 lesions, 73 lesions <1 cm). At 40 mAs, subjective noise in mediastinal window settings were graded as unacceptable in baseline images and acceptable in postprocessed images. Visibility of smaller structures improved from suboptimal visibility in baseline images at 40 mAs to excellent in postprocessed images at 40 mAs. No major artifacts were seen due to NLAF postprocessing, except for minor beam hardening artifacts not affecting diagnostic decision-making (14/22) in both baseline and postprocessed image series. Diagnostic confidence for chest CT was improved to fully confident in postprocessed images at 40 mAs. Compared to baseline images, postprocessing reduced objective noise by 26% (14.2±4.7/19.2±6.4), 31.5% (15.2±4.7/22.2±5.7), and 41.5% (16.9±6/28.9±10.2) at 110 mAs, 75 mAs, and 40 mAs tube current-time product levels. Conclusion: Applications of NLAF can help reduce tube current down to 40 mAs for chest CT while maintaining lesion conspicuity and image quality.